2010
DOI: 10.1093/aob/mcq206
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress induces distinct physiological responses in the two Trebouxia phycobionts of the lichen Ramalina farinacea

Abstract: The better physiological performance of TR9 under oxidative conditions may reflect its greater capacity to undertake key metabolic adjustments, including increased non-photochemical quenching, higher antioxidant protection and the induction of repair mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…In addition, in previous studies we determined that, regardless of the geographic location of this lichen, two genetically and morphologically different Trebouxia algae (provisionally named TR1 and TR9) coexist within every thallus (del Campo et al, 2010;Casano et al, 2011;del Hoyo et al, 2011). TR1 and TR9 show distinct physiological responses to the oxidative stress caused by the ROS propagator cumene hydroperoxide .…”
Section: Introductionmentioning
confidence: 94%
“…In addition, in previous studies we determined that, regardless of the geographic location of this lichen, two genetically and morphologically different Trebouxia algae (provisionally named TR1 and TR9) coexist within every thallus (del Campo et al, 2010;Casano et al, 2011;del Hoyo et al, 2011). TR1 and TR9 show distinct physiological responses to the oxidative stress caused by the ROS propagator cumene hydroperoxide .…”
Section: Introductionmentioning
confidence: 94%
“…These quantitative discrepancies could be explained, at a first glance, by putative differences in ROS-scavenging differences between TR1 and TR9 algae. However, in previous studies [1,14], we have observed that even though basal levels of antioxidant enzymes glutathione reductase, superoxide dismutase and ascorbate peroxidase were significantly higher TR1 than in TR9 (liquid cultures), Pb treatments induced the three enzymes in TR9 while it had no significant effect on those of TR1. In consequence, antioxidant activities were quantitatively similar in both phycobionts under Pb treatments [1].…”
Section: Intracellular Ros Formation and Oxidative Parameters During mentioning
confidence: 58%
“…The Trebouxia phycobionts (provisionally TR1 and TR9) coexisting in R. farinacea thalli showed distinct physiological responses to light intensity, temperature and oxidative stress generated by the ROS propagator cumene hydroperoxide [9,14]. In addition, liquid cultures of TR1 and TR9 were similarly tolerant to lead exposure, but employed different morpho-physiological strategies against the heavy metal [1].…”
Section: Intracellular Ros Formation and Oxidative Parameters During mentioning
confidence: 99%
See 1 more Smart Citation
“…Many chlorolichens contains more than one photobiont. For instance, Ramalina farinacea includes two different Trebouxia photobionts (TR1 and TR9) and isolation of these algae allowed to characterise physiological differences between both of them (Casano et al, 2010;del Hoyo et al, 2011). There are different methods in function of the objective of investigation.…”
Section: Methods For Isolating Lichen Photobiontsmentioning
confidence: 99%